Construct Validity Examination of Life Skills for Primary School Students in Iran - Ghombavani, Fatemeh Parasteh; Alwi, Nor Hayati; Ghadi, Ibrahim; Tarmizi, Rohani Ahmad (Mediterranean Journal of Social Sciences, 2012)
This study addressed the issue of assessing the psychology properties of the construct validity for the life skillsinstrument. The life skills instrument consists of 31 Likert-type items measuring ten skills in five areas, namely self-awarenessand empathy, interpersonal relationship and communication, creative thinking and critical thinking, decision-making and problemsolving, coping with stress and emotion. The study involves 215 primary school students in Iran. The findings showed that theLife skills have satisfactory construct validity with five factors extracted and confirmed by confirmatory factor analyses. TheCronbach’s alpha values are supported construct validity, which the results indicates high validity and reliability for theinstrument to measure life skills.